Multi-exposure laser speckle contrast imaging using a high frame rate CMOS sensor with a field programmable gate array - Sun, Shen; Hayes-Gill, Barrie R.; He, Diwei; Zhu, Yiqun; Morgan, Stephen P. (Optical Society of America, 2015)
A system has been developed in which multi-exposure Laser Speckle Contrast Imaging (LSCI) is implemented using a high frame rate CMOS imaging sensor chip. Processing is performed using a Field Programmable Gate Array (FPGA). The system allows different exposure times to be simulated by accumulating a number of short exposures. This has the advantage that the image acquisition time is limited by the maximum exposure time and that regulation of the illuminating light level is not required. This high frame rate camera has also been deployed to implement laser Doppler blood flow processing enabling direct comparison of multi-exposure laser speckle contrast imaging and Laser Doppler Imaging (LDI) to be carried out using the same experimental data. Results from a rotating diffuser indicate that both multi-exposure LSCI and LDI provide a linear response to changes in velocity. This cannot be obtained using single-exposure LSCI unless an appropriate model is used for correcting the response.